2009
DOI: 10.1016/j.neuron.2009.08.018
|View full text |Cite
|
Sign up to set email alerts
|

SUN1/2 and Syne/Nesprin-1/2 Complexes Connect Centrosome to the Nucleus during Neurogenesis and Neuronal Migration in Mice

Abstract: Nuclear movement is critical during neurogenesis and neuronal migration, which are fundamental for mammalian brain development. Although dynein, Lis1, and other cytoplasmic proteins are known for their roles in connecting microtubules to the nucleus during interkinetic nuclear migration (INM) and nucleokinesis, the factors connecting dynein/Lis1 to the nuclear envelope (NE) remain to be determined. We report here that the SUN-domain proteins SUN1 and SUN2 and the KASH-domain proteins Syne-1/Nesprin-1 and Syne-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
500
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(518 citation statements)
references
References 64 publications
18
500
0
Order By: Relevance
“…Freshly dissected eyes were enucleated and two eye cups were homogenized in 200 µl TNP buffer [48] to make retina protein extracts. Preparation of cell lysates from other tissues, co-immunoprecipitation and western blot analyses with antibodies against DIC, DHC, and DLIC1 were performed according to the procedures described previously [48].…”
Section: Immunoprecipitation and Western Blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshly dissected eyes were enucleated and two eye cups were homogenized in 200 µl TNP buffer [48] to make retina protein extracts. Preparation of cell lysates from other tissues, co-immunoprecipitation and western blot analyses with antibodies against DIC, DHC, and DLIC1 were performed according to the procedures described previously [48].…”
Section: Immunoprecipitation and Western Blot Analysesmentioning
confidence: 99%
“…Preparation of cell lysates from other tissues, co-immunoprecipitation and western blot analyses with antibodies against DIC, DHC, and DLIC1 were performed according to the procedures described previously [48]. For quantification of protein levels, appropriate film exposures were scanned, the density of bands were determined with image J and normalized to band intensity for GAPDH.…”
Section: Immunoprecipitation and Western Blot Analysesmentioning
confidence: 99%
“…Experiments in knockout mice revealed that the SUN-domain proteins SUN1 and SUN2 and the KASHdomain proteins Syne-1/Nesprin-1 and Syne-2/Nesprin-2 play an important role in regulating interkinetic nuclear migration as well as neuronal migration in mice. Syne-2 is connected to the centrosome through interactions with both dynein/dynactin and kinesin complexes (Zhang et al 2009). It is likely that as they mediate the microtubule binding to the nucleus, that they serve as transducers of the forces applied to them by the motors to the nucleus (Fig.…”
Section: Molecular Motors and The Cytoskeletonmentioning
confidence: 99%
“…These defects resulted from a depletion of neural progenitor cells. Nesprin-2 is thought to couple the LINC complex to the centrosome and this link has an impact on the crucial functions of the centrosome during brain development [16,26]. The loss of KASH-domain containing Syne 2 isoforms also affected nuclear migration in photoreceptor cells and caused a reduced thickness of the outer nuclear layer in the eye[27].…”
Section: Introductionmentioning
confidence: 99%